Innovations in bio-inspired computing and applications : proceedings of the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017) held in Marrakech, Morocco, December 11-13, 2017 /: proceedings of the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017) held in Marrakech, Morocco, December 11-13, 2017. ([2018]) - Unknown
No abstract available